On the relation between the Itô and Stratonovich integrals in Hilbert spaces - Twardowska, Krystyna; Nowak, Agata (Annales Mathematicae Silesianae, 2004)
We examine the relation between the Itô and Stratonovich integrals in Hilbert spaces. A transition formula has origin in the correction term of the Wong-Zakai approximation theorem.